Rethinking Religious Freedom in the Frame of the First Principle of Pancasila and Human Rights Law - Meliyani Sidiqah (JURNAL AKTA, 2024)
Freedom of religion is a fundamental human right that cannot be revoked by any authority, including the state. However, the reality demonstrates that acts of intolerance and discrimination persist, perpetrated not only by individuals within society but also by state officials and law enforcement officers against certain communities. These actions undermine the realization of religious freedom. The implementation of this right practically lacks adequate protection from the state. The core issue lies in the interpretation of human existence and the role of religion, and the understanding of religious freedom in Indonesia. This article seeks to deepen the comprehension of human existence and religion while uncovering the obscured dimensions of religious freedom in the Indonesian context. This study employs normative juridical research with an interdisciplinary approach, examining secondary data. The findings indicate that humans and freedom are inherently connected. Religion offers individuals freedom, while humans, in turn, embody sacred values. Religion is not a tool to secure basic services from the state. Indonesia must protect human rights so that everyone can practice religious freedom. Indonesia must foster an atmosphere of tolerance, while also promoting a high level of democracy to all sectors of society through self-reflection as individuals seek personal freedom.